Objective analysis of the effectiveness of facial massage using breakthrough computed tomographic technology: A preliminary pilot study. Issue 3 (13th April 2022) - Okuda, Itsuko; Takeda, Mizuho; Taira, Masahiro; Kobayashi, Toyoaki; Inomata, Ken; Yoshioka, Naoki
Abstract: Background: Facial massage is empirically known to be associated with morphological changes, such as improvements in facial sagging. However, quantified objective evaluations of massage‐induced changes have not been performed to date. This preliminary pilot study aimed to verify the effectiveness of facial massages by using breakthrough computed tomographic technology. Materials and methods: Five healthy adult volunteers (three women and two men; age, 29–37 years) were enrolled, and computed tomography (CT) examinations using a 320 detectors‐spiral CT system known as 320‐multidetector‐row CT (MDCT) were performed before and after facial massages. Each participant performed a self‐massage twice daily for 2 weeks. Massage‐induced changes in the cheeks and the superficial musculoaponeurotic system (SMAS) were analyzed by two radiologists on a workstation with a high‐accuracy imaging analysis system. Results: After facial massage, the malar top became thinner by −0.8% ± 0.45% and shifted cranially and horizontally over a distance of 3.9 ± 1.94 mm. The SMAS‐height, defined as the highest vertical distance of the SMAS, increased by 2.6% ± 2.6%. The change rate in cheek thickness and SMAS‐height showed a significant correlation ( r = −0.63; P < 0.05). These changes were attributed to the lifting and tightening effects of facial massage. Conclusion: We conducted a detailed analysis of the effects of facial massages by using the breakthrough CT technology. Our results provide useful information for beauty treatments and could contribute to the collection of objective scientific evidence for facial massages.